An Individual With Hearing Preservation and Bimodal Hearing Using a Cochlear Implant and Hearing Aids Has Perturbed Sound Localization but Preserved Speech Perception - Snandan Sharma; Lucas H. M. Mens; Ad F. M. Snik; A. John van Opstal; Marc M. van Wanrooij (Frontiers in Neurology, 2019)
This study describes sound localization and speech-recognition-in-noise abilities of a cochlear-implant user with electro-acoustic stimulation (EAS) in one ear, and a hearing aid in the contralateral ear. This listener had low-frequency, up to 250 Hz, residual hearing within the normal range in both ears. The objective was to determine how hearing devices affect spatial hearing for an individual with substantial unaided low-frequency residual hearing. Sound-localization performance was assessed for three sounds with different bandpass characteristics: low center frequency (100–400 Hz), mid center frequency (500–1,500 Hz) and high frequency broad-band (500–20,000 Hz) noise. Speech recognition was assessed with the Dutch Matrix sentence test presented in noise. Tests were performed while the listener used several on-off combinations of the devices. The listener localized low-center frequency sounds well in all hearing conditions, but mid-center frequency and high frequency broadband sounds were localized well almost exclusively in the completely unaided condition (mid-center frequency sounds were also localized well with the EAS device alone). Speech recognition was best in the fully aided condition with speech presented in the front and noise presented at either side. Furthermore, there was no significant improvement in speech recognition with all devices on, compared to when the listener used her cochlear implant only. Hearing aids and cochlear implant impair high frequency spatial hearing due to improper weighing of interaural time and level difference cues. The results reinforce the notion that hearing symmetry is important for sound localization. The symmetry is perturbed by the hearing devices for higher frequencies. Speech recognition depends mainly on hearing through the cochlear implant and is not significantly improved with the added information from hearing aids. A contralateral hearing aid provides benefit when the noise is spatially separated from the speech. However, this benefit is explained by the head shadow in that ear, rather than by an ability to spatially segregate noise from speech, as sound localization was perturbed with all devices in use.